MicroRNA, HPV AND CERVICAL CARCINOGENESIS: MOLECULAR ASPECTS AND PROSPECTS OF CLINICAL APPLICATION - P. A. Arkhangelskaya; E. V. Bakhidze; I. V. Berlev; R. B. Samsonov; M. K. Ivanov; A. V. Malek (Сибирский онкологический журнал)
Cervical cancer is one of the most common cancers of the female reproductive system and a leading cause of mortality in women worldwide. Epidemiologic and experimental data have clearly demonstrated a causal role of Human Papillomavirus in cervical carcinogenesis. Determination of HPV DNA of high carcinogenic risk is relevant screening tool to identify patients with an increased risk of cervical neoplasia. However, the positive predictive value of such an analysis is not high enough. Analysis of additional indicators of infection (viral load, the ratio of episomal and integrated forms of the virus, the duration of its persistence) can be used to improve the diagnostic and prognostic value of HPV testing. In the last decade, studies have shown that HPV induces specific changes in miRNA profile of the infected cell, which reflect the phasing of the disease and may have diagnostic / prognostic value. This review summarizes the current understanding of cellular changes in the profile of microRNAs, caused by infection with HPV, given the known examples of microRNA involvement in cervical carcinogenesis and the perspectives of the possible use of microRNAs as biomarkers in the diagnosis of cervical cancer.